Abberent expression of NOR1 protein in tumor associated macrophages contributes to the development of DEN‐induced hepatocellular carcinoma. Issue 6 (4th January 2018) - Chen, Shengnan; Zheng, Pan; Wang, Wei; Yi, Mei; Chen, Pan; Cai, Jing; Li, Junjun; Peng, Qian; Ban, Yuanyuan; Zhou, Ying; Zeng, Zhaoyang; Li, Xiaoling; et al.
Abstract : Hepatocellular carcinoma (HCC) is the most common primary tumor of the liver and the sixth most common lethal cancer worldwide. Recent evidences demonstrated that oxidored nitro domain containing protein 1 (NOR1), a putative tumor suppressor gene, is overexpressed in human HCC tissues. However, the role of NOR1 in HCC development remains unclear. Here, we described that NOR1 protein level is elevated in HCC and is associated with poorer clinical outcome. However, ecotopic overexpression of NOR1 protein in human HCC cell line HepG2 cells had no effect on cells proliferation, migration, and clonality. Immunofluoresence assay indicates NOR1 protein is mainly expressed at CD163 positive M2 tumor associated macrophages (TAMs). To explore the role of NOR1 in the development of HCC, we interrogated the susceptibility of mice lacking the NOR1 gene to DEN‐induced hepatocarcinogenesis. NOR1 deficient mice displayed resistance to DEN‐induced HCC. We also demonstrate that mNOR1 protein is enriched in F4/80 positive Kupffer cells (KCs) infiltrated in DEN induced murine HCC tissues. Loss of NOR1 led to increase of iNOS whereas decrease of Arg1, Ym1 expression in KCs. Overexpression of NOR1 in THP‐1 macrophages led to decrease of iNOS but increase of Arg1. Mechanistic investigations showed that inflammatory cytokines IL‐6, TNF‐α production, and NF‐κB activation were also decreased in NOR1 knockout mice exposed to DEN treatment. Our data suggested that NOR1 is overexpressed in HCC associated TAMs and promotes M2 alternative polarization. Genetic deletion of NOR1 in mice leads to impairment of IL‐6 production and NF‐κB activation, which in turn attenuates DEN‐induced HCC development. Abstract : Abberent expression of NOR1 protein contributes to the DEN‐Induced hepatocellular carcinoma oncogenesis through promoting tumor associated macrophages M2 alternative polarization.